Ambivalence, Mimicry, and the Third Space: Homi K. Bhabha’s Theory in Dear Martin - Annisa; Suardi (International Journal of English and Applied Linguistics (IJEAL), 2025)
This study analyzes ambivalence, mimicry, and the third space in the racial identity of Justyce McAllister in the novel Dear Martin using Homi K. Bhabha’s postcolonial theory. The method employed is descriptive qualitative, focusing on how the main character experiences identity tension, adapts to a predominantly white environment, and deconstructs racial stereotypes through the concept of the third space. The findings reveal that Justyce’s racial ambivalence is reflected in 202 dialogue excerpts, which expose the tension between his desire to be accepted by white society and his connection to the Black community. This ambivalence gives rise to identity confusion and awareness of both individual and institutional racism. The analysis of mimicry, found in 188 dialogue excerpts, shows that Justyce adapts to dominant social norms to avoid conflict, but at the cost of his identity and psychological well being. Meanwhile, the analysis of the third space concept in 176 dialogue excerpts indicates that Justyce uses it to deconstruct the racial stereotypes that constrain him. This space helps him negotiate his identity, understand justice, and develop a more critical perspective on social injustice. Thus, this study affirms that Homi K. Bhabha’s theory can be applied to understand the complexity of racial identity in Dear Martin, particularly in relation to ambivalence, mimicry, and the third space as strategies of adaptation and resistance against racial stereotypes.